2000
DOI: 10.1192/bjp.176.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Childhood predictors of adult medically unexplained hospitalisations

Abstract: Unexplained hospital admissions are associated with certain childhood experiences of illness, but defined physical illness in childhood is not a risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 25 publications
3
46
0
3
Order By: Relevance
“…Thus, these cognitive and behavioural factors might predict a pattern of response that leads to deconditioning, which is an important candidate for perpetuating fatigue. More distal predictors of an individual's response to illness may also be important, and we have recently shown that unexplained symptoms in adulthood are associated with childhood experiences of illness (Hotopf et al 1999(Hotopf et al , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these cognitive and behavioural factors might predict a pattern of response that leads to deconditioning, which is an important candidate for perpetuating fatigue. More distal predictors of an individual's response to illness may also be important, and we have recently shown that unexplained symptoms in adulthood are associated with childhood experiences of illness (Hotopf et al 1999(Hotopf et al , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The incidence of IBS is equal between adults and adolescents but the symptoms of IBS usually start in the early childhood or adolescence. [12][13][14][15] Although IBS is not a life-threatening condition for most patients it is a chronic recurrent illness that is often accompanied by severe impairment in health related quality of life (HRQOL) measures like decrease in concentration, energy, vitality and self-confidence, and increase in absence rates from work stations. [16][17][18] The patients with IBS have impaired HRQOL that is significantly worse than that of patients with diabetes mellitus or end-stage renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Further, there is evidence from large birth cohort studies to suggest that children with various pain syndromes, in particular abdominal pain and headache, experience an increased risk of abdominal pain, headache, musculoskeletal pain, and a variety of adverse psychological outcomes in later life (22)(23)(24)(25). In adults, recent studies have highlighted the importance of psychological factors, physical/mechanical factors, and a number of episode-specific characteristics such as the duration of symptoms, radiating sciatic pain, and physical limitation (26 -28).…”
Section: Introductionmentioning
confidence: 99%